2021
DOI: 10.1038/s41467-021-21711-5
|View full text |Cite
|
Sign up to set email alerts
|

N4BP1 negatively regulates NF-κB by binding and inhibiting NEMO oligomerization

Abstract: Many immune responses depend upon activation of NF-κB, an important transcription factor in the elicitation of a cytokine response. Here we show that N4BP1 inhibits TLR-dependent activation of NF-κB by interacting with the NF-κB signaling essential modulator (NEMO, also known as IκB kinase γ) to attenuate NEMO–NEMO dimerization or oligomerization. The UBA-like (ubiquitin associated-like) and CUE-like (ubiquitin conjugation to ER degradation-like) domains in N4BP1 mediate interaction with the NEMO COZI domain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…A report showed that N4BP1 inhibits TLR-mediated activation of NF-κB by interacting with the NF-κB signaling essential modulator (NEMO, also known as IκB kinase γ) to suppress NEMO dimerization. 119 In this scenario, the RNase domain of N4BP1 is not required for the control of NF-κB in macrophages. Another study showed that N4BP1 is expressed in the skin and further upregulated during psoriasis.…”
Section: Regnase-4 In the Control Of T Cell Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…A report showed that N4BP1 inhibits TLR-mediated activation of NF-κB by interacting with the NF-κB signaling essential modulator (NEMO, also known as IκB kinase γ) to suppress NEMO dimerization. 119 In this scenario, the RNase domain of N4BP1 is not required for the control of NF-κB in macrophages. Another study showed that N4BP1 is expressed in the skin and further upregulated during psoriasis.…”
Section: Regnase-4 In the Control Of T Cell Activationmentioning
confidence: 99%
“…N4BP1 inhibits replication of HIV-1 and lentiviruses in T cells and macro- Recent studies demonstrate that N4BP1 participates in the regulation of host innate immune responses. 118,119 N4bp1 −/− mice develop mild inflammation and have exacerbated TLR-dependent inflammatory responses. 118 These mice also show diminished numbers of T cells in the peripheral blood.…”
Section: Regnase-4 In the Control Of T Cell Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified mouse or human neutrophils were adjusted to 1×10 6 cells/mL and added into 48 well plates. The cells were cultured with cytokines or inhibitors according to the following concentrations: [17][18][19][20][21][22][23][24] rmIL-1β (100 ng/mL), rmIL-4 (10 ng/mL), rmIL-6 (50 ng/mL), rmIL-10 (20 ng/ mL), rmIL-13 (50 ng/mL), rmIL-21 (50 ng/mL), rmIL-33 (100 ng/mL), LPS (100 ng/mL), rmIFN-γ (100 ng/mL), rmTNF-α (100 ng/mL), rmTGF-β1 (5 ng/mL), rmGM-CSF (40 ng/mL), rmG-CSF (100 ng/mL), rmIL-2 (10 ng/ mL). rmIL-12 (5 ng/mL), IL-17A (100 ng/mL), rmIL-18 (25 ng/mL), rmIL-25 (20ng/mL), JNK inhibitor (SP600125, 10 or 20 μM), A selective ERK inhibitor (PD98059, 10 or 20 μM), NF-κB inhibitor (10 or 20 μM), and P38 inhibitor (SB203580, 10 or 20 μM).…”
Section: Polarization Of Neutrophils In Vitromentioning
confidence: 99%
“…C: Z-scores of the best-scoring siRNAs for selected previously known and newly identified pathway regulators. Hits include VPS28 (Mamińska et al, 2016), CYLD (Trompouki et al, 2003), NFKBIA (Haskill et al, 1991), TRAF3 (Vallabhapurapu et al, 2008), N4BP1 (Shi et al, 2021), TANK (Wang et al, 2015), SENP1 (Lee et al, 2011;Shao et al, 2015), PARG (Cortes et al, 2004), RELA (Li et al, 2001), TIFA (Fu et al, 2018), CHUK (Colomer et al, 2019), TRAF6 (Hinz et al, 2010) and IKBKG (Mabb et al, 2006) for expected factors. D: Representative relative luciferase units (RLU) of the differential counter screen of the 320 pre-selected hits are shown.…”
Section: Statistical Testsmentioning
confidence: 99%